Developing Scotland’s First Green Health Prescription Pathway: A One-Stop Shop for Nature-Based Intervention Referrals - Marx, Viola; More, Kimberly R. (Frontiers in Psychology, 2022)
Introduction Lifestyle modifications are part of comprehensive treatment plans to help manage the symptoms of pre-existing chronic conditions. However, behavior change is notoriously difficult as patients often lack the necessary support. The present manuscript outlines the development of a Green Health Prescription pathway that was designed to link patients with appropriate lifestyle interventions (i.e., nature-based interventions) and to support attendance. Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was undertaken in three focus groups (i.e., National Health Service healthcare professionals, service-users, and nature-based intervention delivery partners) to highlight areas of strength and weakness within the proposed pathway prior to delivery. The SWOT analyses revealed that the pathway was supported by all three focus groups. Weaknesses and threats were identified including sustainability of nature-based interventions in terms of funding, the need to connect patients with appropriate interventions based on their physical and mental health needs, and the requirement to have a “one-stop shop” for information to ensure that the pathway was accessible for all service-users and healthcare professionals. Results were addressed and considered throughout the development of the pathway. Discussion The Green Health Prescription pathway was launched in 2019 and gave patients the ability to receive a prescription from a healthcare professional, community service, or to self-refer. The pathway allows patients to contact a consultant, via a telephone service, who is trained to match them with a programme that the patient believes will be enjoyable and that fits their treatment needs. Data collection to assess the efficacy of the pathway is ongoing.